Analysis of the Influence of Knowledge Management, Digital Adoption, and Technology-Based Training on Organizational Performance - Didik Widiantoro; Loso Judijanto; Suhartono Suhartono; Susatyo Adhi Pramono; Dominica Maria Ratna Tungga Dewa; Bernadin Maria Noenoek Februati (Malikussaleh University, Aceh, Indonesia, 2025)
The manufacturing industry in Indonesia faces significant challenges in the era of digitalization and technological transformation. To remain competitive, companies need to implement strategies that support improved organizational performance. This study aims to analyze the influence of knowledge management, digital adoption, and technology-based training on organizational performance. The study was conducted using a quantitative approach with a survey method of 130 employees from six manufacturing companies in Indonesia. Data were collected through closed-ended questionnaires and analyzed using multiple linear regression. The results of the analysis indicate that all independent variables significantly influence organizational performance. Knowledge management is the most dominant factor with a beta coefficient value of 0.438, followed by digital adoption (0.386) and technology-based training (0.342). The Adjusted R² value of 0.675 indicates that the three variables explain 67.5% of the variation in organizational performance. Furthermore, all proposed hypotheses are accepted based on significance values below 0.05. This study confirms the findings of previous studies, which demonstrate the importance of knowledge and technology management in driving organizational competitiveness. These findings provide practical recommendations for manufacturing company management to integrate knowledge management systems, accelerate technology adoption, and increase the effectiveness of technology-based training to improve organizational performance sustainably.